1996
DOI: 10.1207/s15324826an0303&4_5
|View full text |Cite
|
Sign up to set email alerts
|

Development of memory and learning skills in school-aged children: a neuropsychological perspective

Abstract: While there have been significant theoretical advances in child neuropsychology in recent years, progress in clinical practice has been restricted owing to a lack of well standardized, developmentally appropriate assessment techniques. This paper addresses this issue, with the focus on memory and learning skills. These abilities are targeted because they are frequently impaired following brain damage in childhood, and because they are of central importance to the efficient acquisition of cognitive, educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 32 publications
1
37
1
5
Order By: Relevance
“…Verbal learning and memory was assessed with Rey Auditory-Verbal Learning Test (RAVLT) (Rey, 1964), where the child has five trials to listen to and learn as many words as possible and immediately recall this list after interference , and Story Recall (Christensen, 1979;Anderson & Lajoie, 1996), where the child listens to two short stories and then tries to immediately recall them correctly. Spatial learning and memory was assessed with the Spatial Learning Test (Lhermine & Signoret, 1972;Anderson & Lajoie, 1996).…”
Section: Measures Of Neuropsychological Functions (Studies III and Iv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal learning and memory was assessed with Rey Auditory-Verbal Learning Test (RAVLT) (Rey, 1964), where the child has five trials to listen to and learn as many words as possible and immediately recall this list after interference , and Story Recall (Christensen, 1979;Anderson & Lajoie, 1996), where the child listens to two short stories and then tries to immediately recall them correctly. Spatial learning and memory was assessed with the Spatial Learning Test (Lhermine & Signoret, 1972;Anderson & Lajoie, 1996).…”
Section: Measures Of Neuropsychological Functions (Studies III and Iv)mentioning
confidence: 99%
“…Spatial learning and memory was assessed with the Spatial Learning Test (Lhermine & Signoret, 1972;Anderson & Lajoie, 1996). The children were asked to memorise and recall the positions of nine pictures on a wooden board.…”
Section: Measures Of Neuropsychological Functions (Studies III and Iv)mentioning
confidence: 99%
“…Score increased prominently between the ages 6 and 15, followed by a smaller increase between the ages 16 and 17 years of age. Past research has found that for the ROCF immediate and delay recall, there is a large increase in scores between the ages 6 to 12 followed by smaller increases between the ages of 12 and 17 (Anderson & Lajoie, 1996;Boone, Lesser, Hill-Gutierrez, Berman, & D'elia, 1993;Caffarra, Vezzadini, Dieci, Zonato, & Venneri, 2002;Chervinsky, Mitrushina, & Satz, 1992;Chiulli, Haaland, Larue, & Garry, 1995;Denman, 1984;Hartman & Potter, 1998;Kramer & Wells, 2004;Meyers & Meyers, 1995, 1996Miatton, Wolters, Lannoo, & Vingerhoets, 2004;Pontón et al, 1996;Van Gorp, Satz, & Mitrushina, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Digit span (Anderson & Lajoie, 1996). Forwards digit span was administered as a measure of short-term memory.…”
Section: Rey Complex Figure Test (Rcft As Described Inmentioning
confidence: 99%